The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/3853409
|View full text |Cite
|
Sign up to set email alerts
|

Proscillaridin A Promotes Oxidative Stress and ER Stress, Inhibits STAT3 Activation, and Induces Apoptosis in A549 Lung Adenocarcinoma Cells

Abstract: Cardiac glycosides are natural compounds used for the treatment of cardiovascular disorders. Although originally prescribed for cardiovascular diseases, more recently, they have been rediscovered for their potential use in the treatment of cancer. Proscillaridin A (PSD-A), a cardiac glycoside component of Urginea maritima, has been reported to exhibit anticancer activity. However, the cellular targets and anticancer mechanism of PSD-A in various cancers including lung cancer remain largely unexplored. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 46 publications
(66 reference statements)
5
36
1
Order By: Relevance
“…STAT3, a member of the STAT family, is involved in oncogenic transformation and progression in some cancer types, including lung cancer . The antiapoptotic protein, BCL‐XL, is a key protein downstream of the STAT3 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…STAT3, a member of the STAT family, is involved in oncogenic transformation and progression in some cancer types, including lung cancer . The antiapoptotic protein, BCL‐XL, is a key protein downstream of the STAT3 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…STAT3, a member of the STAT family, is involved in oncogenic transformation and progression in some cancer types, including lung cancer. 11,12 The antiapoptotic protein, BCL-XL, is a key protein downstream of the STAT3 signaling pathway. 18 In the current study, we found that t-STAT3, p-STAT3, and BCL-XL were significantly decreased in A549 cells treated with SCU in concentration-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, c-Jun N-terminal kinase (JNK) and p38 are prominent members involved in apoptosis. 28,29 In previous studies, it has been demonstrated that high level of ROS generation in cells induces apoptosis via JNK pathway. 8 In our study, Brv-A increased phosphorylation of JNK and p38 without affecting total JNK and p38 ( Figure 5A and B).…”
Section: Brv-a Induces P38 and Jnk Activation And Inhibits Stat3 Signmentioning
confidence: 99%